Answer:
f(-2) = 5/9
Explanation:
* lets explain the problem
∵ f(x) = 5(3)^x
- It is an exponential function
- (3) is the base of the function
- x is the exponent
- To find f(-2) means substitute x by -2
∵
![f(x)=5(3)^(x)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/uarxdqwbfa7jwknhk5wvxcqie0tmwbw1sc.png)
∵ x = -2
∴
![f(-2)=5(3)^(-2)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/1vdzk7kvqfnqguwij9m00n32uryh7anlsi.png)
- If the power of the base is negative we can change its sign to
positive by reciprocal the base
# Ex:
![(a)^(-n)=((1)/(a))^(n)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/jv4sstdmglms1b2es14z7ra4dv5ounwmcy.png)
- Lets do that withe the base 3 and power -2
∵
![(3)^(-2)=((1)/(3))^(2)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/64ve0c9bx9fa0yb0babn2gcjjkezo5ifr5.png)
∴
![f(-2)=5((1)/(3))^(2)=5((1)/(9))=(5)/(9)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/maijr9rm85grb08b5byhskyzx1wb77yv2h.png)
* f(-2) = 5/9